Enhancing smoking cessation in Mexico using an e-Health tool in primary healthcare - Guadalupe Ponciano-Rodríguez; Luz Myriam Reynales-Shigematsu; Rosibel Rodríguez-Bolaños; Javier Pruñonosa-Santana; Francisco Cartujano-Barrera; Ana Paula Cupertino (Salud Pública de México, 2018)
Objective. To evaluate an e-Health tool designed to enhance smoking cessation in Mexico in primary healthcare. Materials and methods. Smokers 18 years of age and older were recruited in the waiting room of two primary healthcare clinics in Mexico City. Participants used an e- Health smoking cessation tool that included smoking-related assessments, education on pharmacotherapy, and motivational videos. A follow-up assessment was conducted at 12 weeks week on smoking status. Logistic regression models were performed to identify factors associated with smoking cessation or consumption reduction. Results. A total of 132 smokers were enrolled in the study. At follow-up, 23.5% of participants self-reported smoking cessation. Among those who did not quit smoking, 65.0% decreased the number of cigarettes. Factors associated significantly with smoking cessation were: being a non-daily smoker, being interested in quitting smoking, having low level of physical dependence, and participating in cessation treatment. Conclusions. The e-Health tool produced a high rate of smoking cessation. Better outcomes are obtained when this tool is used with conventional cessation programs.